ТЕНДЕНЦІЇ РОЗВИТКУ ВИЩОЇ ПЕДАГОГІЧНОЇ ШКОЛИ УКРАЇНИ У СВІТЛІ ВИМОГ БОЛОНСЬКОГО ПРОЦЕСУ (Педагогіка вищої та середньої школи, 2022)
The article contains the analysis of works of scientists dedicated to the development of higher pedagogical education in Ukraine from 1985-to 2003. The main tendencies, directions, achievements, and problems of this development are characterized.